Photovoltaic powered uninterrupted power supply based on pic microcontroller - Mahrizal Masri (School of Computer and Communications Engineering, 2016)
The main objective of thesis is to design a photovoltaic powered UPS system. It contents of solar charger, transfer switch and inverter. It is due to the battery of PV powered UPS system is charged by photovoltaic module via the solar charger and the PV module performance depends on the solar irradiation, thus the solar irradiation is important to be analyzed. For this case, the scopes of thesis are limited on; analysis of solar irradiance as energy potential of PV powered UPS system is only done in Perlis, Northern Malaysia; the solar charger is developed and controlled by voltage regulator LM2575T-ADJ and PIC microcontroller, respectively. The voltage regulator LM2575T-ADJ gives the circuit output voltage of 12 V to 14 V and output current of 3 A, thus this solar charger is applied only for 12 V charger system. But by adding a multiple current circuit, this solar charger can flow PV current up to 24 A; the transfer switch of PV powered UPS system is developed by PIC microcontroller to detect the failed main power source, but to transfer electrical energy from failed main power source to inverter source still use 12 V DC relay and low speed accuracy. It still is categorized in a stand by UPS system; the inverter of powered UPS system has three level voltage waveform. It has still rich harmonic compared to the sine wave voltage. But the peak voltage angle, of three level voltage waveform can be adjusted to obtain the lowest current total harmonic (CTHD).